RE: Comments on: Further studies of Bolivian crocidolite-Part IV: Fibre width, fibre drift and their relation to mesothelioma induction: Preliminary findings, by Ilgren EB, van Order DR, Lee RJ, Kamiya YM, Hoskins JA ebph 2015; 12 (2) e11167 - Stefania Boccia; Carlo La Vecchia (Epidemiology, Biostatistics and Public Health)
RE: Comments on: Further studies of Bolivian crocidolite-Part IV: Fibre width, fibre drift and their relation to mesothelioma induction: Preliminary findings, by Ilgren EB, van Order DR, Lee RJ, Kamiya YM, Hoskins JA Epidemiology Biostatistics and Public Health 2015; 12 (2), e11167